(untitled) (Acta Polytechnica CTU Proceedings, 2016)
Motivated by the hype around driverless cars and the challenges of the sensor integration and data processing, this paper presents a model for using a XBox One Microsoft Kinect stereo camera as sensor for mapping the surroundings. Today, the recognition of the environment of the car is mostly done by a mix of sensors like LiDAR, RADAR and cameras. In the case of the outdoor delivery challenge Robotour 2016 with model cars in scale 1:5, it is our goal to solve the task with one camera only. To this end, a three-stage approach was developed. The test results show that our approach can detect and locate objects at a range of up to eight meters in order to incorporate them as barriers in the navigation process.